The sustainable management of byproducts of the steel industry: Egypt case study - Karem Mahmoud, Amina Mahmoud (AUC Knowledge Fountain, 2019)
In society today, the world is faced with multiple challenges within the realm of sustainability in the economic, social, and environmental sectors. Egypt has also been faced with challenges that have been growing over the decades that require a vision that will put forward mitigation efforts and recommendations. Egypt’s steel industry has been rapidly and vastly expanding over the past decade due to an overall increase in demand in steel, this is also linked to the fact that with population growth the supply demanded increases which in turn requires that the demand meet. The growing steel market has sparked the emergence and opening of a number of newly introduced companies who have joined this viable production sector. As steel production in Egypt is increasing, the country must also adapt and develop ways to sustainably treat the by- products of steel production, which are harmful to the environment, society, and the economy. The types of waste generated from steel production include byproducts that are usually left unrecycled or that are thrown away. These byproducts include slag and dust. Sustainable methods of reusing byproducts generated by steelmaking plants would help develop more viable production cycles for steel plants in Egypt, especially with their current uses that are not being employed correctly. However, to date, no sustainable practices for the reuse of steelmaking byproducts have been implemented by the steel making industry in Egypt. By researching ways in which steel byproducts are dealt with in other countries and assessing how such methods are suitable in the Egyptian context, this thesis will make important recommendations for a more sustainable management of byproducts of steel in Egypt. This thesis will employ a case study method and pros and cons will be discussed to examine which approach is the optimal choice for the industry in Egypt. Further research regarding the procedures of implementations, the current and potential difficulties that will be faced and the lessons learnt from case studies abroad will also be taken into consideration. Ultimately, this thesis shows positive results from the mathematical calculations that have forecasted the potential reuse profits of slag and dust. This will imply that these methods are viable for Egypt to implement as recommendations for the next steps forward. In addition to that looking and learning from countries methodologies abroad that have implemented vast methods of byproduct dealings and their impacts on the three pillars of sustainability.